Novel Design of Electromagnetic Bandgap Using Fractal Geometry. (14th March 2013) - Phuong, Huynh Nguyen Bao; Chien, Dao Ngoc; Tuan, Tran Minh
Abstract : A novel electromagnetic bandgap (EBG) structural design based on Fractal geometry is presented in this paper. These Fractals, which are the Sierpinski triangles, are arranged to repeat each 60° to produce the hexagonal unit cells. By changing the gap between two adjacent Sierpinski triangles inside EBG unit cell, we can produce two EBG structures separately that have broadband and dual bandgap. By using the suspending microtrip method, two arrays 3 × 4 of EBG unit cells are utilized to investigate the bandgap of the EBG structures. The EBG operation bandwidth of the broadband structure is about 87% and of the dual-band structure is about 40% and 35% at the center bandgap frequencies, respectively. Moreover, a comparison between the broadband EBG and the conventional mushroom-like EBG has been done. Experimental results of the proposed design show good agreement in comparison with simulation results.